Design and Kinematics Analysis of (2SPS/U)&(2SPS/RR) Type Parallel Humanoid Manipulator - Zhiguang Ma; Kangkang Wang; Leile Zhang; Shaowei Jia; Can Chen (Jixie chuandong)
As the existing bionic humanoid manipulator has large inertia impaction， poor continuity and stability， a novel humanoid manipulator is presented. The humanoid arm can simulate the wrist joint， elbow joint and shoulder joint. The (2SPS/U)&(2SPS/RR) two-stage coupling parallel mechanism is used to drive each joint action In order to obtain its inverse and forward kinematics， the closed vector method and Newton iteration method are used to calculate the positive and negative kinematics solutions of the two-stage parallel mechanism， and then the mechanism configuration of the whole artificial arm is simplified. Based on the D-H method， the forward and inverse position solutions of the whole mechanism are given and validated.